E-VOTING SYSTEM BASED ON BLOCKCHAIN - Setiawan AR, Adnan
Well-designed e-voting can improve the security of ballots, ensure voter privacy and speed up calculation processing. The challenge of e-voting is how to maintain data integrity and voter privacy but allow for transparency. Some studies use several cryptographic techniques to ensure voter privacy but do not guarantee data integrity. Likewise, the use of blockchain as a ballot box to maintain the integrity and transparency of votes but blockchain is not involved in the entire e-voting phase. In this thesis, analysis and design are carried out so that all stages of the selection will be carried out in the blockchain system. At each of these stages, an analysis of the challenges that will be faced and the threats that need to be mitigated are also carried out. Several cryptographic techniques are applied to smart contracts to detect double voting and for the calculation process. The results of the study show that data integrity is achieved because every data change on the blockchain can be tracked and will also result in failed transaction commits if the data in the ledger of each peer is inconsistent. Voter privacy can be guaranteed by using the LRS scheme in signature generation and double voting detection, but it causes computation to be higher as the number of voters increases. The performance of counting ballots using the homomorphic encryption scheme is not significantly affected by the large number of ballots because the decryption process is only carried out for the summation results.